Analysis of the Influence of the Maqasid Shariah Index on Profitability in Sharia Commercial Banks Listed on the IDX for the 2018-2025 Period - Abdur Rahman Hakim; Haprilla Putri Giantama; Muh Rifai Arsyad (Journal JEKAMI, 2026)
The positive growth of the Islamic banking industry in Indonesia demands not only financial growth but also the holistic implementation of Islamic values. This study examines the effect of the Maqasid Syariah Index (MSI) on the financial performance of Islamic Commercial Banks in Indonesia, addressing the empirical inconsistencies and data gaps found in previous literatures. Utilizing an exploratory research design with a quantitative approach, this study evaluates annual report data from Islamic banks. The data analysis technique employed is simple linear regression, focusing on the relationship between Maqasid Syariah Index (X1​) as the independent variable and Return on Assets (ROA, Y) as the dependent variable. Prior to hypothesis testing, classical assumption tests were conducted, confirming that the residual data is normally distributed and free from heteroscedasticity based on the Glejser test (p=0.913>0.05). The coefficient of determination (R Square) is 0.447, indicating that the Maqasid Syariah Index accounts for 44.7% of the variance in ROA, while the remaining 55.3% is influenced by other factors outside the model. The partial significance test (t-test) yields a t-count of −4.921 with a significance value of 0.000 (p<0.05). Consequently, H0​ is rejected and H1​ is accepted, establishing the regression equation Y=7.738−9.704(X1​). The empirical findings conclude that the Maqasid Syariah Index has a significant negative effect on Return on Assets. This demonstrates a short-term trade-off where prioritizing social welfare, justice, and public interest (maslahah) leads to a reduction in immediate financial profitability.